ANÁLISE DAS PRÁTICAS DE GESTÃO AMBIENTAL EM PROPRIEDADES RURAIS DO MUNICÍPIO DE SANTA MARGARIDA DO SUL-RS - Oliveira, Karen de; Senna, Ana Julia Teixeira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705492 Man’s quest for survival has always affected the natural environment. Environmentaltransformations got increasingly intense with the advent of industrialization in towns and theintroduction of agricultural mechanization in the rural areas. The activities involving agriculturaland livestock production, if not managed properly, could affect environmental stability and,therefore, interfere with sustainability at farm level. The objective of this research is tocharacterize the environmental management practices common in rural holdings located in themunicipality of Santa Margarida do Sul. Initially, a bibliographic survey on environmentalmanagement, rural extension and sustainability was conducted. Afterwards, an interview itinerarywas set up, articulated with theoretical references, geared towards rural producers. Data analysisshowed that most rural producers are concerned about rural environmental management,however, some of them have not yet adopted it on their holdings, that is why it was ascertainedthat it is utterly important to implement environment education and extension initiatives directedtowards rural producers.